Governing complex environmental policy mixes through institutional bricolage: lessons from the water-forestry-energy-climate nexus. Issue 5 (3rd September 2022) - Leong, Ching; Howlett, Michael; Lai, Theodore
ABSTRACT: Policy mixes come in many shapes and sizes. This poses many challenges to policy design, especially when mixes extend across sectors and have multiple levels. This is the case with the Water-Forest-Energy-Climate (WFEC) nexus, a complex policy mix that involves not only significant cross-sectoral linkages and the potential complementarities and conflicts which are examined in other articles in this special issue, but also deals with sectors which involve significant national and trans-national elements. This complex multi-sector, multi-level policy assemblage also lacks the cohesion provided by a treaty-based international regime which allows multi-level co-ordination and integration of policy designs in areas such as trade or finance. In such policy non-regime or weak regime complexes, regional agreements and the negotiated nature of interactions within such agreements (which we see as a form of 'policy bricolage') are critical but overlooked factors affecting policy success.